Improving Accountability in Temple Asset Management Through the Integrated Hindu Asset Management Information System Regulation - I Made Bayu Andika (JURNAL ILMIAH GEMA PERENCANA, 2026)
The low quality of governance of Hindu houses of worship in Indonesia, particularly regarding the uncertainty of legality and certification of land assets, has become a crucial issue that threatens the physical existence of holy places from the risk of land disputes and third-party claims. This policy paper aims to formulate a strategy for governance transformation by strengthening the digital administration system to ensure legal certainty for religious assets. The policy methodology used in this study is a qualitative-descriptive approach with multi-criteria analysis (MCA) techniques and the William N. Dunn scoring method, which evaluates various regulatory alternatives based on aspects of effectiveness, efficiency, and accountability. Based on the analysis results, this paper recommends the urgency of establishing a Minister of Religious Affairs Regulation on the Integrated Hindu Asset Management Information System (SIMA-H) as an instrument for integrating spatial and legal data capable of mitigating the risk of disputes preventively. The implementation of this policy is supported by theoretical support for stewardship and certainty of agrarian law, and requires institutional synergy through strengthening the legal literacy of house of worship managers. The scoring results indicate that digitizing asset management is the most responsive step in addressing data disparities and the weakness of traditional documentation that has been based on oral tradition.